PHYTOCHEMICAL SCREENING AND GC-MS ANALYSES OF AQUEOUS EXTRACTS OF Aframomum melegueta (ALLIGATOR PEPPER) SEEDS AND FRUITS AS POTENTIAL AGENTS FOR MANAGING FISH HEALTH - Abe, Grace Osisienemo; Oniye, Sonnie Joshua; Auta, Jehu; Onimisi, Hassan Umaru; Yusuf, Abdullateef (FUDMA Journal of Sciences, 2026)
Aframomum melegueta (Roscoe) K. Schum is an herbaceous tropical perennial from the Aframomum genus, which is part of the Zingiberaceae family (the ginger family) within the angiosperm of the Plantae kingdom. The seeds and whole fruit of Aframomum melegueta were extracted separately with distilled water (1:10 w/v) by maceration for 24 hours at room temperature. The extracts were filtered, concentrated at 40°C, and stored at 4 °C until use. The resulting aqueous extract was subjected to qualitative and quantitative phytochemical analysis. The qualitative phytochemical screening revealed the presence of alkaloids, cardiac glycosides, saponins, phenolic compounds, tannins, steroids, carbohydrates, flavonoids and terpenoids. Quantitative analysis demonstrated significant concentrations of carbohydrates (13.94% and 13.94%), phenolic compounds (5.18% and 6.80%), and flavonoids (5.64% and 4.15%) from the seeds and whole fruits, respectively. The GC-MS analysis eluted twenty-two (22) bioactive compounds from A. melegueta seed extract and seventeen (17) bioactive compounds from the whole fruit aqueous extract. These bioactive compounds may act synergistically to offer strong antimicrobial, antioxidant and anti-inflammatory potential in aquaculture nutrition as well as manage the health of fish.